Impact of Gender and Language Learning In Educational Settings - Kaissi, Nadia (International Journal of Language and Literary Studies, 2024)
Given the significant impact of gender and language learning in educational settings, it is critical to understand how students’ learning styles and gender contribute to their academic achievement and gender interaction in English language classes, especially in the university context. This research paper highlights the impact of gender differences on English language learning at the university level, especially in the Moroccan tertiary education context. The study aims to provide insight into how students’ learning styles and gender perceptions affect their English language learning. Data was collected through an online survey and distributed to 60 master’s and doctoral students. The findings revealed a significant link between gender differences and English learning, in particular how male and female students prefer to work with classmates of the same or different gender to improve their language skills.